Insight into Pyroelectricity and Phase Transitions in Ferroelectrics from Nonequilibrium Approach: The Case of PbTiO3. Issue 10 (19th August 2022) - Lynch, Kelli Ann; Meng, Tepie; Ponomareva, I.
Abstract: Computational methodology is proposed to simulate time dependent temperature variations via thermostat approach. The methodology is applied to study pyroelectricity under nonequilibrium conditions in prototypical ferroelectric PbTiO3 . It is found that at room temperature the nonequilibrium effects in pyroelectricity begin manifesting above 1.0 THz and originate from the overlap with the intrinsic soft mode frequency. Therefore, the proposed computational methodology can be used to predict equilibrium pyroelectric response by choosing a frequency of temperature variation below the intrinsic polar mode frequencies for the material. Probing the dynamics of ferroelectric phase transition with the proposed methodology revealed that it takes about a nanosecond for the computational supercell to undergo phase transition. It is concluded that computational techniques capable of simulating picoseconds can be used to compute pyroelectric response from nonequilibrium dynamical approach while those that can reach nanoseconds are suitable for simulating phase transitions in ferroelectrics. Abstract : Computational methodology for time dependent sinusoidal temperature variations is proposed and applied to study nonequilibrium pyroelectric response and dynamics of ferroelectric phase transitions. The polarization response to temperature variations in GHz–THz frequency range is revealed.